A statistical quality control study on SC & C Cosmetic Co., Inc. - Esteban, Hazel; Esquivias, Eugene; Gatpandan, Ana Carmela (Diliman, Quezon City College of Engineering, 2005)
SC&C Cosmetech Co., Inc is now the exclusive manufacturer of quality products of Johnson & Johnson Philippines like Johnson's Pure Essentials Face Powder, Johnson's BAND-AID Isopropyl Alcohol, Johnson's Baby Powder, Johnson's Baby Oil, Johnson's Baby Lotion, Johnson's Baby Cologne, and Johnson's Baby Bath. The product of Johnson's Baby Oil is a relatively new ndertaking. It produces three variations of Johnson's Baby Oil (in forms of 25ml, 50ml, and 125ml bottles). It is essential for the production process to be very efficient in terms of output and costs. The management wishes to know if fill volume is maintained within the minimum acceptable amount thus maximizing production volumem and if the process is capable in still reducing the specification limits. The group was therefore assigned, upon the onset of the project to address these concerns using concepts and tools in statistical quality control. Usiung past data provided by the company, the group executed control charting, capability analysis and other problem solvieng tools such as the FMEA and Ishikawa diagram to identify, analyze, and address the problems. It was found out that the process is in control after
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Quality Control